As idéias industrialistas de José da Silva Lisboa e de João Severiano Maciel da Costa : um estudo comparativo (1808-1821) - Carvalho, Suelem Halim Nardo de (2009)
Our objective in this study is to analyze comparatively the thought of industrialist Jose da Silva Lisboa, Viscount of Cairu (1756-1835), and Joao Severiano Maciel da Costa, Marquis of Queluz (1769-1833), in the period between 1808 and 1821. Both authors were important figures in brazilian History at the begining of the nineteenth century, that argued different positions in the field of political-ideological conceptions. Viscount of Cairu, advocate of liberal thought in Brazil, believed in free trade as a legitimate way to stimulate the gradual development of industry in the country. Maciel da Costa, a conservative figure, realised that only with the adoption of state protectionism would create the conditions for industrialization in the country. The debate between the two authors began the discussion, present among us today, on industrial policy wich would be more appropriate to industrialize the country: protectionism or liberalism?